Metacognitive skills in relation to learning achievement in dentistry entrants from a public university in the Peruvian highlands (Revista Estudios Psicológicos, 2024)
The aim of the study conducted was to relate metacognitive skills to learning achievement in freshmen entering the Dentistry program at the National University of the Altiplano in Puno - Peru. The study adopts a quantitative approach, with a correlational level and a non-experimental design. It is observational, prospective, and cross-sectional. The sample consisted of a total of 45 freshmen, selected through consecutive non-probabilistic sampling, as all individuals in the population who met the inclusion and exclusion criteria were considered. The technique used to measure the variable of metacognitive skills was a survey, with the instrument used being the Metacognitive Awareness Inventory (MAI). Learning achievement was measured using documentary analysis through reviewing the averages achieved by the freshmen. The results showed that there is a relationship between metacognitive skills and learning achievement in freshmen (p=0.000). Metacognitive skills in their knowledge dimension were predominantly at a high level (67.4%), as were those in their cognition regulation dimension (60.5%). Freshmen's learning achievement was predominantly acceptable (67.4%). Both male (20.9%) and female (37.2%) students predominantly exhibited a high level of metacognitive skills, and similarly, students from both public and private schools mainly had a high level of metacognitive skills. The study concludes that there is a statistically significant relationship between metacognitive skills and learning achievement, which supports the implementation of induction programs for freshmen before they begin their university academic activities, considering not only academic aspects but also metacognitive skills.
Keywords: metacognitive skills; newcomers; metacognition; university students